Exploring science education students' understanding of nuclear physics concepts through field study implementation with non-stationary calorimetry methods - Muhammad Nur Hudha; Kadek Dwi Hendratma Gunawan; Dian Sinta Khusnul Ramawati; Salsabila Kholifahtun Nisa’ (Momentum: Physics Education Journal, 2025)
This study explores the implementation of field studies using non-stationary calorimetric methods to understand the learning experience of science education students on the concept of nuclear physics. The study involved 72 science education S1 students who participated in an experiment to determine thermal power at the Kartini Reactor facility through a descriptive qualitative approach. The field study used reactor operation at a constant power of 100 kW by shutting down the cooling system to demonstrate the principle of heat accumulation. Students collected temperature data from three digital thermometers every 5 minutes for 35 minutes, then performed a linear regression analysis to calculate thermal power. Thematic analysis from student observations, interviews, and reflections reveals the development of conceptual understanding in four key areas. The students managed to calculate thermal power of 107.99 kW, 106.40 kW, and 109.08 kW with deviations in acceptable tolerances. The findings show that hands-on experience facilitates an understanding of energy conservation principles, heat transfer mechanisms, and experimental validation techniques. This study reveals students' ability to develop connections between theoretical concepts of nuclear physics and practical applications through authentic learning experiences.